Current Challenges and Possibilities for Improving Physical Education Management Program in a Normal University in China - Liu, Zhisheng (Pacific International Journal, 2025)
This study investigates the current challenges and potential improvements in physical education (PE) management at Huanggang Normal University in the post-pandemic educational landscape. As schools transition back to face-to-face learning, the need to address the decline in students’ physical health and to enhance the delivery of PE programs has become increasingly urgent. Using a quantitative-comparative-correlational research design, the study surveyed 70 PE teachers at the university, examining their assessments of existing difficulties in budget management, resource utilization, professional development, teaching strategies, and curriculum innovation. The demographic profile of respondents was also analyzed in relation to their perceptions. Findings reveal that PE management remains challenging across multiple domains, with particularly low satisfaction in areas such as funding allocation, communication of available resources, and relevance of professional development. Nevertheless, teachers acknowledged moderate possibilities for improvement, suggesting a cautious optimism toward reforming current systems. Based on the results, a development plan was proposed emphasizing financial optimization, enhanced resource access, teacher training, diversified instructional methods, and holistic wellness integration. The study provides valuable insights into the systemic issues affecting PE programs in higher education and offers practical strategies for improving the quality and effectiveness of physical education in a post-pandemic context.